Crime Combating Policy of Carding in Indonesia in the Political Perspective of Criminal Law - Muhammad Isnaeni Puspito Adhi; Eko Soponyono (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The development and progress of science and technology lead to the emergence of cybercrime. One form of cybercrime is carding. Carding is a crime of using or stealing other people's credit cards through cyberspace. This paper discusses the process of criminal law enforcement against carding crimes based on current positive law and future carding crime prevention policies in terms of the political perspective of criminal law. The method used was a normative juridical research method. The discussion shows that criminal law enforcement efforts against carding crimes have been regulated through the Law on Information and Electronic Transactions, but these arrangements cannot overcome carding crimes in Indonesia, so there is a need for a formulation policy that specifically regulates carding crimes. The policy of dealing with carding crime in the future is reviewed from the perspective of criminal law politics, namely through penal and non-penal efforts. Efforts should be made to socialize cyber law for the people of Indonesia that can support the use of credit cards as a means of payment in online transactions in a responsible manner and have a strong legal basis.